Kyai's Prophetic Leadership in Effectiveness of Learning in Pesantren - Junaris, Imam; Baharun, Hasan; Andriesgo, Johan; Zamroni, Zamroni (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to understand prophetic leadership in realizing effective learning from the perspective of Kurt Lewin at pondok pesantren. This study uses a phenomenological approach, where the researcher tries to understand the meaning behind the phenomenon through in-depth interviews, observation, and documentation. The data sources of this research were obtained from the information submitted by the informants, the results of observations and documents, and the results of the study of several theories taken from reputable scientific books and journals. The data analysis was carried out circularly, from data collection, data presentation, and data reduction to concluding. The results of the study indicate that prophetic leadership in realizing effective learning from the perspective of Kurt Lewin at pondok pesantren is carried out through; first, unfreezing, which consists of changing motivation, feeling towards change, preparation for change; second, moving, namely the movement towards something new or the latest developments; third, refreezing maintains the change results. This study concludes that Kyai's prophetic leadership in making learning effective in Islamic boarding schools in the perspective of Kurt Lewin's change management must be carried out in a planned, systematic and earnest manner concerning the values of humanization, liberation, and transcendence, considering that change is intended to improve the quality of education in Islamic boarding schools. The research has implications for the importance of leaders in responding to the dynamics of existing changes, both internal to the organization and external to the organization.